Developing Student Moderation Attitudes through Self-Control-Based Class Management - Rozi, Fathor; Rahman, Fawait Syaiful; Rosi, Fathor; Nu'man, Agus; Iskandar, Iskandar (Universitas Muhammadiyah Surakarta, 2023)
The escalating prevalence of intolerance and radicalism within diverse student age cohorts has become a pronounced area of concern. This phenomenon is ostensibly linked to the suboptimal implementation of moderation education in educational institutions. Consequently, the primary objective of this investigation is to scrutinize the application of self-control-based classroom management in Islamic elementary schools as a means of cultivating moderation attitudes among students. The research was executed at an Islamic elementary school in East Java, Indonesia, employing a multifaceted approach encompassing observations, interviews, and documentation for data collection. The analytical framework of Miles and Huberman was adopted for data analysis, with data triangulation serving as a mechanism for ensuring data validity. The instructional strategy employed by the observed school in nurturing moderation attitudes via self-control-based classroom management comprises several pivotal activities. These include student grouping, discouraging the use of sarcasm within the madrasa environment, fostering group discussions, and incentivizing academic achievement. The design of these activities is strategically oriented towards prompting students to manifest self-control across their behavior, cognitive processes, and decision-making while upholding the core values of al-'adl, tawazun, and tasamuh. This research holds substantial significance in its contribution to the enhancement of students' behavioral acumen, cognitive capacities, and decision-making proficiencies. The overarching impact is realized through the instillation of respect for others, the eradication of discriminatory tendencies, and the cultivation of a culture of mutual affection among students.